2009
DOI: 10.1002/cjoc.200990353
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of β‐Cyclodextrin‐Felbinac Inclusion Complex

Abstract: The crystal structure of the inclusion complex of β-cyclodextrin (β-CD) synthesized with felbinac (4-biphenylacetic acid) was determined by single crystal X-ray diffraction at 150 K. The complex contains two β-CDs, two felbinac molecules, twenty-two water molecules in the asymmetric unit, and could be formulated as (C 42 H 70 O 35 ) 2 •(C 14 H 12 O 2 ) 2 •22(H 2 O). In the crystal lattice, the two β-CD moieties form a head-to-head dimer jointed through hydrogen bonds, and the felbinacs that interact by face-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Our investigation into the association behavior of synthetic AHLs with β‐CD began with 1 , principally because the association of its carboxylic acid precursor (4‐biphenylacetic acid, BPAA) with β‐CD is well‐known through both solubility studies and X‐ray crystallography [39–41] . The crystal structure of the {β‐CD:BPAA} inclusion complex, solved by Wang and co‐workers, indicated that the biphenyl region of BPAA docks within the host's hydrophobic cavity [41] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our investigation into the association behavior of synthetic AHLs with β‐CD began with 1 , principally because the association of its carboxylic acid precursor (4‐biphenylacetic acid, BPAA) with β‐CD is well‐known through both solubility studies and X‐ray crystallography [39–41] . The crystal structure of the {β‐CD:BPAA} inclusion complex, solved by Wang and co‐workers, indicated that the biphenyl region of BPAA docks within the host's hydrophobic cavity [41] .…”
Section: Resultsmentioning
confidence: 99%
“…Our investigation into the association behavior of synthetic AHLs with β‐CD began with 1 , principally because the association of its carboxylic acid precursor (4‐biphenylacetic acid, BPAA) with β‐CD is well‐known through both solubility studies and X‐ray crystallography [39–41] . The crystal structure of the {β‐CD:BPAA} inclusion complex, solved by Wang and co‐workers, indicated that the biphenyl region of BPAA docks within the host's hydrophobic cavity [41] . This SAHLA also has biological relevance as a broad spectrum QS antagonist, capable of inhibiting the TraR 15 ( Agrobacterium tumefaciens , Ti plasmid replication and conjugation), [42–44] LuxR 15 ( Vibrio fischeri , bioluminescence), [45,46] and QscR [47] ( P. aeruginosa , “antivirulence′”) [48] .…”
Section: Resultsmentioning
confidence: 99%
“…Although the single-crystal structures of inclusion complexes between felbinac and both heptakis-(2,3,6-tri-O-methyl)-βcyclodextrin and β-cyclodextrin have been published (Harata et al, 1992;Wang et al, 2009), that of the pure compound has not been reported. The molecular structure is shown in Figure 1.…”
Section: S1 Commentmentioning
confidence: 99%
“…Hydrogen bonds between carboxylic acid groups of felbinac are disrupted in the published felbinac-cyclodextrin structures (Harata et al, 1992;Wang et al, 2009). In the inclusion complex between felbinac and heptakis-(2,3,6-tri-Omethyl)-β-cyclodextrin (Harata et al, 1992), no dimers are formed; in that between felbinac and β-cyclodextrin (Wang et al, 2009), face-to-face π-π stackings form the basis for dimer formation.…”
Section: S1 Commentmentioning
confidence: 99%
See 1 more Smart Citation